Aesthetic Disruptions: Critical Surveillance Art and the Unsettling of Surveillance - Wooley, Justin (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
In the field of surveillance studies, scholars have focused on the use of art to offer an aesthetic intervention into the operation of surveillance systems. Scholars have used the term “surveillance art” to capture a genre of artwork that draws critical attention to the use of surveillance technologies. Through Sadie Barnette’s work The FBI Project (2016–ongoing), this article argues that Barnette’s work offers a critical intervention into the field of surveillance art by foregrounding the racial logic of surveillance. By taking up the literature on surveillance art and drawing on Torin Monahan’s (2022) notion of critical surveillance art, the article presents Barnette’s artwork as a model for contending with the racial tenor of surveillance regimes. As a way of exposing and redressing the racial violence of surveillance, Barnette’s instantiation of surveillance art offers new ways of imagining and perceiving the world and, as such, poses the possibility of intervening in the operation of our contemporary surveillance system. Ultimately, the article provides a reading of Barnette’s FBI series as offering co-constructive interventions into both the genre of surveillance art and the structure of racial surveillance. Barnette’s artwork acts as a form of critical surveillance art, which offers an aesthetic experience that moves beyond the critique of surveillance mechanisms and offers a view of the sites of resistance that exceed the bounds of surveillance.